Modified CTAB method for high-quality genomic DNA extraction from ship barnacle (Balanus sp.) - MISHRA, ARCHANA; ROY, UTSA; KUSHWAHA, SIMRAN KRISHNAKANT; LULLA, SUHASINI; PRAJAPATI, REETI (The Indian Journal of Animal Sciences, 2019)
Presence of high amount of polysaccharide and polyphenolic compounds in barnacles restricts the isolation of high molecular weight good quality DNA. CTAB, which is a detergent used to isolate DNA from high polysaccharide containing plants, is used in this study to extract quality DNA from ship barnacle. This modified CTAB method is simple, efficient and quick enough to be carried out within 2 h. Taking DNAzol Â® isolated DNA as a reference, restriction digestion and PCR was performed to prove the absence of any enzyme inhibitory substances in the isolate. Traditional phenol-chloroform and salting out method failed to even isolate the DNA from barnacle sample. The molecular weight of the modified CTAB extracted DNA was higher than that of DNAzol Â® extracted DNA which makes it better candidate for analyses like whole genome sequencing.